Heart of the West : Husband for hire - Wiggs, Susan (Toronto ; New York : Harlequin, 1999)
Lost Springs Ranch was famous for turning young mavericks into good men. So word that the ranch was in financial trouble sent a herd of loyal bachelors stampeding back to Wyoming to put themselves on the auction block!
Keywords: Problem youth -- Rehabilitation -- Fiction; Class reunions -- Fiction; Divorced women -- Fiction; Physicians -- Fiction; Love stories